Enhancing Cognitive Fit: Exploring the Potential of Mixed Reality for Developing Mental Rotation Skills - Piri, Zeynep; Kaplan, Goknur; Cagiltay, Kursat (Informa UK Limited, 2024)
Mixed Reality is a promising venue for spatial ability training, allowing participants to engage in problem-solving through gesture-based interactions with holographic objects. 3-D measurement of learning in Mixed Reality environments may result in a better cognitive fit than 2-D. This mixed-method study measures and enhances mental rotation ability and investigates user experience in Mixed Reality. To assess mental rotation ability, we adapted the Purdue Spatial Visualization Test:Rotation for Microsoft HoloLens 2, creating a measurement tool for our Mixed Reality-based training program, Holomental. Comparing 2-D and 3-D tests, we explored how stimulus dimensionality influences accuracy and cognitive load. Our findings indicate that Holomental enhances mental rotation performance, both in 2-D and 3-D. Cognitive load in the 3-D test was lower than in the 2-D test. Semi-structured interviews revealed participants’ appreciation for the representational and interactional affordances of the training environment. This study provides valuable insights into the effectiveness of 3-D spatial training, with implications and suggestions for future design considerations.